Geographic Analysis of Mobile Stroke Unit Treatment in a Dense Urban Area: The New York City METRONOME Registry. Issue 24 (17th December 2019) - Kummer, Benjamin R.; Lerario, Mackenzie P.; Hunter, Madeleine D.; Wu, Xian; Efraim, Elizabeth S.; Salehi Omran, Setareh; Chen, Monica L.; Diaz, Ivan L.; Sacchetti, Daniel; Lekic, Tim; Kulick, Erin R.; Pishanidar, Sammy; et al.
Abstract : Background: Mobile stroke units (MSUs) reduce time to intravenous thrombolysis in acute ischemic stroke. Whether this advantage exists in densely populated urban areas with many proximate hospitals is unclear. Methods and Results: We evaluated patients from the METRONOME (Metropolitan New York Mobile Stroke) registry with suspected acute ischemic stroke who were transported by a bi‐institutional MSU operating in Manhattan, New York, from October 2016 to September 2017. The comparison group included patients transported to our hospitals via conventional ambulance for acute ischemic stroke during the same hours of MSU operation (Monday to Friday, 9 am to 5 pm) . Our exposure was MSU care, and our primary outcome was dispatch‐to‐thrombolysis time. We estimated mean differences in the primary outcome between both groups, adjusting for clinical, demographic, and geographic factors, including numbers of nearby designated stroke centers and population density. We identified 66 patients treated or transported by MSU and 19 patients transported by conventional ambulance. Patients receiving MSU care had significantly shorter dispatch‐to‐thrombolysis time than patients receiving conventional care (mean: 61.2 versus 91.6 minutes; P =0.001). Compared with patients receiving conventional care, patients receiving MSU care were significantly more likely to be picked up closer to a higher mean number of designated stroke centers in a 2.0‐mile radius (4.8 versus 2.7, P =0.002). In multivariable analysis, MSU care was associated with a mean decrease in dispatch‐to‐thrombolysis time of 29.7 minutes (95% CI, 6.9–52.5) compared with conventional care. Conclusions: In a densely populated urban area with a high number of intermediary stroke centers, MSU care was associated with substantially quicker time to thrombolysis compared with conventional ambulance care.